Influence of flooded foam jets’ motion parameters on subsurface extinguishing of fires in tanks with petroleum products - Voitovych, Tetiana; Kovalyshyn, Vasyl; Novitskyi, Yaroslav; Voytovych, Dmytro; Pastukhov, Pavlo; Firman, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2020)
One of the safest ways to extinguish fires in tanks with petroleum and petroleum products is subsurface extinguishing. For this mode, a foam concentrate with fluorinated stabilisers is used, the aqueous solution of which is able to spread and cover the surface of petroleum and petroleum products with a thin film. The article presents a mathematical model of the movement of a flooded non-free foam jet in a motor fuel medium, which adequately describes the real physical processes that occur during subsurface fire extinguishing in vertical steel tanks. The motion parameters of flooded low-foam foam jets in a tank with motor fuel were determined as those that would be optimal for transporting foam through the thickness of the fuel to its surface. It was specified that the movement of the flooded foam jet is characterised by a significant attenuation (from 36 to 1.5 m/s) of the initial velocity with its subsequent increase due to Archimedes’ principle. High values of the initial velocity of the jet lead to destruction of the foam and, accordingly, worsen fire extinguishing. A decrease in the initial velocity of the foam jet at a given flow rate should be carried out by increasing the corresponding number of foam jets with an initial velocity in the range from 2 to 3 m/s. Foam jets should be placed around a circle of a radius at which their mutual influence would be preserved, and the velocity of the combined foam jet should not exceed the maximum values recommended for a particular foam concentrate (3–5 m/s). It helps to improve the stability of the movement of the combined jet, to decrease the destruction of the foam during its movement, and to prevent the movement of the fuel to the combustion surface. The decisions made upon the implementation of the mathematical model are fully consistent with the results obtained during the experimental tests on extinguishing a class B model fire in a designed unit as a reduced version of the RVS-5000 tank.